THE RELATIONSHIP OF RESPONDENT CHARACTERISTICS, KNOWLEDGE, ATTITUDES, AND OWNERSHIP OF LATRINES TOWARDS ITS LOW USE OF LATRINES IN GUNUNG ANYAR VILLAGE, SURABAYA CITY - Anca Laika; Retno Adriyani (The Indonesian Journal of Public Health, 2021)
ABSTRACTGunung Anyar Tambak village had the lowest access to latrines. Some residents defecate in rivers or other places. The study was conducted to determine a relationship of factors and low use of latrines in Gunung Anyar Tambak village. It was observational research with a cross sectional design. Samples were selected from the population through simple random sampling. Guided interviews were conducted to 75 respondents in RW 01 Gunung Anyar Tambak village. The research variables were respondent characteristics (education level and income level), knowledge, attitudes, and latrine ownership. Data analysis was done using the Chi-square test with a degree of confidence at 95%. The results showed a significant relationship between respondent characteristics including education level (p = 0.000), income level (p = 0.000), knowledge (p = 0.006), attitude (p = 0.003), and latrine ownership (p = 0.000) on low use of latrines. The variable with the strongest relationship was latrine ownership. Keywords: education, income, knowledge, attitude, latrine ownership